Integrated QTL and eQTL Mapping Provides Insights and Candidate Genes for Fatty Acid Composition, Flowering Time, and Growth Traits in a F2 Population of a Novel Synthetic Allopolyploid Brassica napus - Li, Ruijuan; Jeong, Kwangju; Davis, John T.; Kim, Seungmo; Lee, Soonbong; Michelmore, Richard W.; Kim, Shinje; Maloof, Julin N. (Frontiers in Plant Science, 2018)
Brassica napus (B. napus, AACC), is an economically important allotetraploid crop species that resulted from hybridization between two diploid species, Brassica rapa (AA) and Brassica olereacea (CC). We have created one new synthetic B. napus genotype Da-Ae (AACC) and one introgression line Da-Ol-1 (AACC), which were used to generate an F2 mapping population. Plants in this F2 mapping population varied in fatty acid content, flowering time, and growth-related traits. Using quantitative trait locus (QTL) mapping, we aimed to determine if Da-Ae and Da-Ol-1 provided novel genetic variation beyond what has already been found in B. napus. Making use of the genotyping information generated from RNA-seq data of these two lines and their F2 mapping population of 166 plants, we constructed a genetic map consisting of 2,021 single nucleotide polymorphism markers that spans 2,929 cM across 19 linkage groups. Besides the known major QTL identified, our high resolution genetic map facilitated the identification of several new QTL contributing to the different fatty acid levels, flowering time, and growth-related trait values. These new QTL probably represent novel genetic variation that existed in our new synthetic B. napus strain. By conducting genome-wide expression variation analysis in our F2 mapping population, genetic regions that potentially regulate many genes across the genome were revealed. A FLOWERING LOCUS C gene homolog, which was identified as a candidate regulating flowering time and multiple growth-related traits, was found underlying one of these regions. Integrated QTL and expression QTL analyses also helped us identified candidate causative genes associated with various biological traits through expression level change and/or possible protein function modification.